Graphene/tourmaline composites as a filler of hot mix asphalt mixture: Preparation and properties. (10th April 2020) - Chen, Qian; Wang, Chaohui; Qiao, Zhi; Guo, Tengteng
Highlights: Graphene could improve the adsorption properties of tourmaline. Graphene/tourmaline composite powder could replace mineral powder. Pavement performance of asphalt mixture is improved by adding composite powder. Composite powder could reduce asphalt smoke emission effectively. Abstract: This study addresses how to reduce the emission of asphalt smoke in the construction process of traditional hot mix asphalt mixture. The graphene/tourmaline composites were prepared based on tourmaline having the effect of adsorbing pollutants. The basic properties of composites and their adsorption effect on asphalt smoke were analyzed. Then, the composite powder was added into the environment-friendly asphalt mixture as filler. And the pavement performances and emission reduction performance of asphalt mixtures were studied. The results indicated that the basic properties of composite powder meet the requirements of specifications about filler in asphalt mixtures. Composite powder could be used to replace part of mineral powder, and the optimum replacement content was 17–20 wt%. The environment-friendly asphalt mixtures can effectively reduce asphalt smoke emission. The reduction rate of emission can reach 76.9–80.5%.